A pinacoteca popular: da imagem ao imaginário nos almanaques de Molina Campos (1931-1945), e Berega (1979-1999) - Betencourt, Maria Goreti (2021)
This doctoral thesis aims to analyze the visual imaginary of the Pampas constructed by two costumbrist artists, the Argentinean Molina Campos (1891-1959) and the Brazilian Berega (1934-2012). The study is dedicated to investigating the imaginary expressed through the medium used by both artists to publicize their work, the Alpargatas and Ipiranga calendars, respectively. The proposed analysis focuses on a methodology created specifically for this purpose, which starts from three large categories, called External, Internal, and Hybrid, whose purpose was to place all the images that were reproduced by the calendars, Alpargatas, from 1931-36 and 1940-45, and Ipiranga, from 1979-1999, except for the years 1985 and 1987, in which there were no productions. These categories were read through different aspects. Namely: the woman, the partnership, the gaucho alone, and the horse. These elements were in turn divided into two panoramas, Introversion and Extroversion. Based on theoretical concepts that structure the questions raised regarding the social imaginary and archetypal relationships, there is also the connection of this same imaginary reproduced in the West by works of art from different periods and authors, creating a fabric that allowed the identification of the visual imaginary of the Pampas. In parallel and with equal importance, there is, finally, the analysis of the kitsch aesthetic component, not investigated from the perspective of the questions that structure the kitch work but rather related to certain aspects of the works studied, observed here only in its emotional component that colors both the works of the artists as a whole, as well as allowing us to understand this constructed imaginary, which is part of what would be the truth and the naivety of the kitsch movement, but which in the works analyzed do not respond to the questions, but rather draw on the emotionality that is part of it and, in the case of the works analyzed, are a source of production of meaning.